Rearranging Production Facilities on Electric Vehicles with the CORELAP Algorithm - Azzahra Rahmadani Wilasto; Muhammad Arif Wibisono (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Electric vehicles as an alternative means of sustainable transportation need to be supported because they can reduce carbon emissions by up to 54% and oil demand by 6.4 MMbpd by 2040 compared to conventional vehicles. GATe (Gadjahmada Airport Transporter Electric) is an electric vehicle based on NEV (Neighborhood Electric Vehicle). GATe car production is carried out at the GATe production facility which is still in the prototype stage. This research reorganizes the production facilities for electric vehicles in GATe (Gadjahmada Airport Transporter Electric) cars for the LRIP (Low Rate Initial Production) stage. The facility layout is designed using a fixed position layout approach, that is, the main product does not move. This research uses the CORELAP method with quantitative evaluation in terms of displacement. It was found that the total displacement using the CORELAP algorithm was 1791.15 m.